Urbanizations closed on a planetary scale - Roitman, Sonia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2016)
The present article is based on the presentation by the author at the opening of the International Seminar on Residential enclosure, organized by the School of Social Work and Human Development at the Universidad del Valle (Cali, Colombia) the días13 and October 14, 2015.